Rapid and specific luminescence sensing of Cu(ii) ions with a porphyrinic metal–organic framework. Issue 72 (23rd August 2017) - Li, Linnan; Shen, Sensen; Lin, Ruoyun; Bai, Yu; Liu, Huwei
Abstract : We herein present a porphyrinic metal–organic framework (MOF) as a highly sensitive fluorescent probe targeting Cu(ii ) ions with a fast response. Abstract : We herein present a porphyrinic metal–organic framework (MOF) as a highly sensitive fluorescent probe targeting Cu(ii ) ions with a fast response. The well-isolated nature of porphyrin moieties within the framework greatly enable accessible recognition sites, which leads to an outstanding detection limit performance of 67 nM among MOF-based materials.